Current state and future prospect of solar energy in an electronic device manufacturing company / Vickneswary Vadivelu - Vickneswary , Vadivelu (2022)
Solar energy system is a potential energy recruitment which helps to reduce greenhouse gases to the environment. The implementation of solar energy in industrial sector assist to achieve the nation’s renewable energy goals. The aim of this research is to analyse the efficiency of photovoltaic system installed at a selected industrial area and its future prospect in terms of economical, social acceptance, and environmental benefits. The research site is located at the city of Shah Alam, Malaysia. The objectives of the research are to determine the total energy generated, analyse cost saving and CO2 reduction from the solar panel installed at the electronic devices manufacturing site. In addition, the acceptance and perspective of renewable energy among the employees were assessed in smaller scale. Furthermore, the challenges in execution and its future prospect were also identified. The methods used in the research work are study case analysis and data collection techniques such as group focus discussion, questionnaire, and utilizing archived data. The research determined the current total energy reduction of year 2019 and 2020 from the installed solar system versus conventional energy usage in 2018. The roadmap of future solar energy installation from year 2022 to 2027 at selected site determined at 19% of CO2 reduction. As conclusion, the study reveals research limitations and suggestions to improve the growth of solar energy at manufacturing site.